PERAN AKTOR DALAM PROSES PEMBENTUKAN DINASTI POLITIK (STUDI KASUS DI KABUPATEN PURWAKARTA) - Dea Arsyad Mujtahid Shibghotulloh; Husin Al-Banjari; Yusa Djuyandi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan Bandung, 2020)
The political phenomenon at the local level which concentrates power limited to the family is interesting to highlight. The power which is only hegemony by the political actor by making his relatives as part of a political dynasty becomes a problem in democratization in Indonesia. Opportunities for the wider community were eroded because the tap to power was blocked by the local elite. The power tree formed by Dedi Mulyadi as a political actor, by making it easier for his wife Anne Ratna Mustika as Purwakarta regent to succeed Dedi Mulyadi, as well as his son Ahmad Habibi Bungsu Maula Akbar as chairman of DPD level II Golkar Party Purwakarta Regency, strengthen Dedi Mulyadi's position as a politician snapper class in the area. By using a qualitative research method approach and taking a case study of Purwakarta Regency, this research illustrates a political dynasty formed by political actors using political skills that are not visible to the public (hidden power). The results showed that the role of political actors based their political skills on knowledge, actors used political party instruments, bureaucracy, and also some Sundanese culture in shaping political dynasties. Moreover, the long-term interests of the actor who desires to become a leader at the level of West Java and National Provinces is an important finding in this article. This necessitates that the actor must be able to secure his power base in Purwakarta Regency. Keywords: Political Dynasty, Political Actors, Hidden Power.